2021
DOI: 10.1002/jobm.202000627
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of the biological characteristics of entomopathogenic fungi in nutrient‐limited and cuticle‐based media

Abstract: Media formulated with insect cuticle (0.5% and 1%; Sphequit Sph®), with a reduction in nutrients (¼ Sabouraud dextrose agar + yeast [SDAY]) and commercial media (potato dextrose agar, Sabouraud dextrose agar) were evaluated for the cultivation of Beauveria bassiana, Cordyceps javanica (Isaria javanica [Bally] Samson & Hywel-Jones), and Metarhizium robertsii. By using principal component analysis, it was determined that the ¼ SDAY and Sph formulations have greater advantages than commercial media for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In line with the aforementioned findings, it was observed that chitosan (a chemical homologue of chitin) could significantly increase carotenoid content in a novel two-stage C. militaris cultivation process [71] (Table 2). In addition, low-nutrient growth media supplemented with insect cuticles increased the pathogenicity of Beauveria bassiana, Cordyceps javanica, and Metarhizium robertsii [33]. These effects are yet to be evaluated for C. militaris, but existing results have already proven a positive impact of insect-based compounds on its growth and productivity.…”
Section: Substrates Nutrient Requirements and Treatments Related With The Cultivation Of C Militarismentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the aforementioned findings, it was observed that chitosan (a chemical homologue of chitin) could significantly increase carotenoid content in a novel two-stage C. militaris cultivation process [71] (Table 2). In addition, low-nutrient growth media supplemented with insect cuticles increased the pathogenicity of Beauveria bassiana, Cordyceps javanica, and Metarhizium robertsii [33]. These effects are yet to be evaluated for C. militaris, but existing results have already proven a positive impact of insect-based compounds on its growth and productivity.…”
Section: Substrates Nutrient Requirements and Treatments Related With The Cultivation Of C Militarismentioning
confidence: 99%
“…Furthermore, in order to optimize C. militaris productivity, many parameters have already been examined through numerous pertinent studies that will be suitably outlined and discussed in the present review. Most of them focused on developing suitable methodologies and interventions to avoid (or minimize) culture degeneration [21][22][23][24][25][26][27][28][29][30][31], on improving ascomata and mycelia production [12,15,[32][33][34][35][36], and/or on enhancing cordycepin output by adopting various approaches and the use of both solid and liquid substrates [12,15,23,32,[37][38][39][40][41][42][43][44][45][46][47]. In addition, the application of genetic engineering breakthrough technologies has resulted in a considerable improvement in C. militaris biomass content in various metabolites, including cordycepin [37,[48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is based on the results reported by Angel-Cuapio et al(2015), who used water hyacinth (Eichhornia crassipes) as a texturizer for improving the production of I. fumosorosea aerial conidia.The application of C. javanica in the eld requires a high quantity of viable conidia with proper quality parameters (Arredondo-Bernal and B. Rodríguez-Vélez, 2020; Montesinos Matías et al, 2020), for example, to control D. citri, at least 2×1012 conidia per hectare are required, using a suspension of 1×10 7 conidia • mL − 1 (Sánchez-González et al, 2015; Adame-García et al, 2021). Unfortunately, in the conventional SSF system, a high yield of conidia usually leads to the formation of conidia with low levels of viability and a decrease in virulence(Jaronski, 2014;Montesinos-Matías et al, 2021). In our study, high yields of conidia…”
mentioning
confidence: 50%
“…Beauveria bassiana strains were cultured on Petri dishes containing SDA, supplemented with 1% SDAY at pH 5.6, and incubated at 27 °C ± 2 °C in darkness [ 25 , 26 ]. After 20 d, conidia were harvested in a 0.05% Tween 80 solution and mixed in a vortex at maximum speed.…”
Section: Methodsmentioning
confidence: 99%
“…Insects were removed from tubes with or without diet and individually transferred to 1.5 mL Eppendorf tubes containing 150 μL of 0.05% Tween 80. Tubes were then gently shaken for one minute and 10 μL was diluted to 1:1000, after which 30 µL was placed in a selective medium for B. bassiana (SMBb) (39 g L −1 potato dextrose agar; BD Bioxon, Guadalajara, Mexico), supplemented with 2.5 g L −1 bacteriological agar (BD Bioxon Mexico), 80 mg L −1 tetracycline (Sigma-Aldrich, St. Louis, MO, USA), 25 mg L −1 cycloheximide (Sigma-Aldrich), 80 mg L −1 streptomycin (Sigma-Aldrich), 80 mg L −1 penicillin (Sigma-Aldrich), and 1 mg L −1 benomyl (Robust R; Promotora Técnica Industrial, Morelos, Mexico) [ 26 , 27 , 28 ]. The inoculum was distributed using Drigalski rods, and Petri dishes were incubated at 25 °C ± 2 °C for 72 h, after which colony-forming units (CFU) were determined.…”
Section: Methodsmentioning
confidence: 99%